Killing Jesus : a history - O'Reilly, Bill.; Dugard, Martin (New York : Henry Holt and Company, 2013)
Details the events leading up to the murder of Jesus of Nazareth. Nearly two thousand years after this beloved and controversial young revolutionary was brutally killed by Roman soldiers, more than 2.2 billion human beings attempt to follow his teachings and believe he is God. Killing Jesus will take readers inside Jesus's life, recounting the seismic political and historical events that made his death inevitable - and changed the world forever. --From publisher's description.
Includes bibliographical resources (pages 275-280) and index.
Keywords: Jesus Christ -- Crucifixion